Fungal gut microbiota dysbiosis in systemic lupus erythematosus - Yang, Ping; Xu, Rui; Chen, Fei; Chen, Shanshan; Khan, Adeel; Li, Liang; Zhang, Xiaoshan; Wang, Yanbo; Xu, Zhipeng; Shen, Han (Frontiers in Microbiology, 2023)
Despite recent developments in our comprehension of how the gut microbiota and systemic lupus erythematosus((SLE) are related). The mycobiome: which is a small but crucial part of the gut microbiota and is involved in hosts’ homeostasis and physiological processes, remained unexplored in SLE. We profiled the gut fungal mycobiota based on internal transcribed spacer region 1 (ITS1) sequencing for the gut microbial DNA from the SLE individuals with lupus nephritis (LN) (n = 23) or without LN (n = 26), and healthy individuals (n = 14) enrolled in The Affiliated Drum Tower Hospital. The ITS sequencing generated a total of 4.63 million valid tags which were stratified into 4,488 operational taxonomic units (OTUs) and identified about 13 phyla and 262 genera. Patients with SLE were characterized with unique fungal flora feature. The fungal microbiomes of the three groups displayed distinct beta diversity from each other. The abundance of fungal dysbiosis was reflected in a higher ratio of opportunistic fungi, as well as the loss of Rhizopus and Malassezia. Moreover, our data revealed superior diagnostic accuracy for SLE with the fungal species (e.g. Candida, Meyerozyma). Correlations between gut fungi and clinical parameters were identified by Spearman’s correlation analysis. Interestingly, Aspergillus in SLE patients was positively correlated with ACR, 24h proteinuria, proteinuria, anti-dsDNA, ANA, and SLEDAI, while Rhizopus was negatively correlated with lymphocytes and Hb. Finally, we successfully cultured the fungi and identified it as Candida glabrata by microscopic observation and mass spectrometry. Collectively, we first explored the highly significant gut fungal dysbiosis and ecology in patients with SLE, and demonstrated the applicability of fungal species as SLE diagnostic tools, signifying that the gut fungal mycobiome-host interplay can potentially contribute in disease pathogenesis.